Self Awareness dan Altruisme pada Guru Tetap dan Guru Honorer - Vivi Niwang Sari; Eben Ezer Nainggolan; Etik Darul Muslikah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to determine the relationship between self-awareness and altruistic behavior and, the differences between the two based on gender, school status, and teacher status both permanent and honorary teachers. The research sample involved 367 participants who were members of the Surabaya teachers group community on social media. The measuring instruments used in the study were the Self-Report Altruism Scale (SRA) (α=0.761) and the self-awareness scale (α=0.826). The results of simple regression analysis show that there is a significant positive correlation between self-awareness and altruism. The test results of the relationship between self-awareness and altruism on gender (male = 117, female = 250) show no significant difference between self-awareness and altruism in men and women. The test results of the relationship between self-awareness and altruism on teacher status (permanent teacher = 180, honorr teacher = 187) show a significant difference between self-awareness and altruism in the group of permanent teachers and honorary teachers. The test results of the relationship between self-awareness and altruism on school status (public school teachers = 136, private school teachers = 231) show no significant difference between self-awareness and altruism in public and private school teachers.